Improve the safety and effectiveness of firelines using Dijkstra's algorithm: model development and implementation during incident - Liu, Zhiwei, author; Wei, Yu, advisor; Thompson, Matthew P., committee member; Kling, Robert, committee member (Colorado State University. Libraries, 2019)
Multiple spatial indices have been developed by past research to evaluate fire management effectiveness and safety concerns and identify fire suppression operation opportunities. In this study, we will use those indices to directly support fireline construction during fire incident management. To identify firelines that can ensure both suppression effectiveness and responder safety, we introduced a raster-surface-based spatial optimization model based on Dijkstra's algorithm. We modified and implemented this algorithm on a network generated from a spatial index derived raster cost surface, and identified paths with the lowest accumulated cost. We also applied indices specified thresholds to avoid locations that may be too risky to conduct fireline construction. We use a portion of northwest Sierra National Forest in California, the USA, as our study site for demonstration, since this area has been well studied in previous research and has abundant data. We tested our model by improving some of the proposed event lines during the 2018 Ferguson Fire suppression for better safety and effectiveness. Testing results confirmed that our model can achieve management objectives. At the end of this study, we identified the limitations of our model, and proposed future works to improve this model to better support fire management.